Spatiotemporal Trends and Attributable Risk Factors of Nasopharyngeal Carcinoma in Southeast Asia (1990–2023): An Ecological Analysis of the Global Burden of Disease Study with Projections to 2050 - Linda Purnama; Priscilla Kapoor; Mustafa Mahmud; Alessandra Navos (Sriwijaya Journal of Otorhinolaryngology, 2025)
Background: Nasopharyngeal carcinoma (NPC) is an Epstein–Barr virus-associated epithelial malignancy with a strikingly uneven geography concentrated in Southeast Asia and southern China. Its region-specific burden, temporal dynamics and attributable risk factors have not been synthesised in a dedicated spatiotemporal ecological analysis. Objective: To characterise NPC burden, trends and attributable risks across Southeast Asia. Methods: We conducted an ecological analysis of Global Burden of Disease (GBD) estimates. Age-standardised incidence (ASIR), mortality (ASMR) and disability-adjusted life-year (DALY) rates for the GBD Southeast Asia region (1990–2021, GBD 2021) and constituent ASEAN countries (to 2023, GBD 2023) were compiled; temporal trends were summarised by the estimated annual percentage change (EAPC); attributable fractions for tobacco, alcohol and occupational carcinogens were obtained from GBD comparative risk assessment; and age-standardised rates were projected toward 2050. Results: In 2021 the Southeast Asia region recorded the highest NPC mortality of any world region (ASMR 1.60 per 100,000). Age-standardised rates declined (EAPC: incidence −0.39, mortality −0.76, DALYs −0.84% per year), yet absolute incident cases more than doubled (6,209 to 13,661; +120%). National ASIR ranged from 1.3 (Cambodia) to 14.2 (Singapore); Indonesia carried the greatest absolute burden (5,163 cases; 4,306 deaths). Incidence rose in Indonesia (EAPC +0.8), Laos (+0.7) and Viet Nam (+0.6). Alcohol-attributable burden increased most steeply (Southeast Asia EAPC +2.27), against declining tobacco- and occupational-attributable rates. Conclusion: Southeast Asia bears the world's heaviest NPC mortality; falling age-standardised rates mask a rising absolute burden and a growing alcohol-attributable component, underscoring the need for Epstein–Barr virus-informed early detection and region-tailored prevention.